Innovation in the construction of educational systems balancing the supply-demand of PhD candidates. An initial research survey - Erkengel, Hazel Ceren; Owoc, Mieczysław Lech (Innowacja w konstrukcji systemów edukacyjnych bilansujących rynek edukacyjny doktorantów. Wstępne studium badań, 2019)
Nowadays, the requirements and expectations of universities are increasing along with globalization. The functions of Research and Development and the doctorate programmes which aim to support education and train the academic staff, came to the fore with globalization. The doctorate programmes in European countries cannot be updated fast enough and quotas for these programs are insufficient in some regions – faster balancing seems to be the must. The Decision Support System (DSS) can be a solution to the problem. In this study, the candidates’ demand of the universities, the public-private organizations and R&D centres are included to a model. As a result DSS will help us identify the need for candidates and develop PhD planning strategies by analysing the current situation of the university policies through the innovative model balancing the supply-demand for PhD candidates – including formulae of doctorate implementation (recently introduced in Poland)
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 1 (51), s. 9-21
Keywords: educational model; decision support system; supply-demand in PhD; model edukacyjny; ekspertowe systemy podejmowania decyzji; podaż-popyt doktorantów